Antioxidant properties of 5 herbal plants based of pharmacophore modelling - Radhakrishnan, Sam Ezekiel; Ariffeen Rosli, Mohammad Farhan; Mursyid Romli, Ardy; Nyawai, Tiara Nales; Asaruddin, Razip (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2016)
Malaysian medicinal plants are known to exert therapeutic effects.We have evaluated some species namely Moringa oleifera (M. Oleifera), Clinacanthus nutans (C. Nutans), Rhodomyrtus tomentosa (R. tomentosa), Arctium lappa(A. lappa) and Sonneratia alba (S. alba) for their antioxidant properties assisted by using pharmacophore modelling approach. Major compounds were displayed from each plantnamely; 3-caffeoylquinic, benzylglucosinolate, kaempferol, leucodelphinidin and quercetin from M.oleifera, adenosine, arctigenin, arctiin, and solasoninefrom A. lappa, 2-cis-entadamine A, phaeophytin, clinamides B, isovitexin, and vitexinfrom C .nutans, 5-hydroxymethylfurfural, alphitolic acid, betulin, methyl gallate, oleanolic acid from S. alba and lupeol, rhodomyrtone A, rhodomyrtone B, rhodomyrtone C and rhodomyrtone D from R. tomentosa.